Therapeutic Potential of Phaleria Macrocarpa Flavonoid Extract Regulating Rantes in Endometriosis - Fany Hardiati Amalia; Amina Diarsy; Sutrisno Sutrisno; Safrina Dewi Ratnaningrum (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Endometriosis is a long-term inflammatory disease that affects women of childbearing age. It is caused by endometrial tissue growing in places other than the uterus. RANTES (Regulated on Activation, Normal T Cell Expressed and Secreted) and other important inflammatory mediators are very important in making the inflammatory responses related to this disorder worse. The aim of this study was to evaluate the impact of the ethanolic extract of flavonoids derived from the fruit of Phaleria macrocarpa (Mahkota Dewa) on RANTES levels in a rat model of endometriosis. Thirty female rats were divided into six groups: one healthy control group, one endometriosis control group, and four treatment groups that received doses of 3.75, 7.5, 15, and 30 mg/rat/day of the extract, respectively. The endometriosis model was established by transplanting myometrial and endometrial tissues from a patient with adenomyosis into the peritoneal cavity of immunosuppressed rats. Once the model was set up, the rats got the extract every day for 15 days in a row. We used the ELISA method to measure RANTES levels and histological and immunohistochemical analyses to look at ERβ expression. The results showed that the endometriosis control group (K+) had the highest levels of RANTES (64.05 ? 1.86 pg/mL). Surprisingly, the group that got 30 mg/rat/day (P4) had the biggest drop in RANTES levels (45.95 ? 1.07 pg/mL). Moreover, an upregulation of ERβ expression was observed in rats with induced endometriosis, evidenced by intensified brown staining, succeeded by a dose-dependent reduction, signifying modulation of estrogenic activity. In summary, the administration of the ethanolic flavonoid extract from Phaleria macrocarpa significantly reduced RANTES levels in rats with endometriosis, underscoring its potential as an alternative treatment for managing inflammation related to endometriosis.?Keyword: Keywords: Phaleria macrocarpa, flavonoid, endometriosis, RANTES